2013
DOI: 10.1182/blood-2013-07-514448
|View full text |Cite
|
Sign up to set email alerts
|

Better leukemia-free and overall survival in AML in first remission following cyclophosphamide in combination with busulfan compared with TBI

Abstract: • In combination with cyclophosphamide, intravenous busulfan is associated with better leukemia-free and overall survival in AML than TBI.Cyclophosphamide combined with total body irradiation (Cy/TBI) or busulfan (BuCy) are the most widely used myeloablative conditioning regimens for allotransplants. Recent data regarding their comparative effectiveness are lacking. We analyzed data from the Center for International Blood and Marrow Transplant Research for 1230 subjects receiving a first hematopoietic cell tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
123
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 158 publications
(130 citation statements)
references
References 47 publications
5
123
1
1
Order By: Relevance
“…Second, as this study is monocentric, patients in this study did not receive various combinations of immunosuppressive agents as usually reported. 25,28,30,35,54 MRD before HSCT had no prognostic value in our cohort. The DFS of patients with negative or positive MRD before HSCT was similar.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Second, as this study is monocentric, patients in this study did not receive various combinations of immunosuppressive agents as usually reported. 25,28,30,35,54 MRD before HSCT had no prognostic value in our cohort. The DFS of patients with negative or positive MRD before HSCT was similar.…”
Section: Discussionmentioning
confidence: 71%
“…DFS usually reported in children transplanted for high-risk leukemia from sibling or unrelated donors vary between 50 and 70%. 25,[27][28][29][30][31][32][33]40 Weiss et al 37 report a similar DFS (84%) using CsA alone as GVHD prophylaxis but in patients transplanted only from MSDs. 37 They also used CsA while targeting a lower and narrower TBC range (80-130 ng/mL) compared with those usually recommended (100-200 ng/mL).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…A recent prospective phase 3 study failed to demonstrate any significant difference in grade 2-4 acute GVHD survival, although patients receiving sirolimus had significantly faster engraftment and less mucositis similar to the experience with MMF. Although they have never been compared in the hematopoietic cell transplant setting, benefits of MMF compared to sirolimus include less adverse effects such as hyperlipidemia, endothelial injury syndromes such as microangiopathy and veno-occlusive disease, which results in the inability to use it with commonly used conditioning such as high dose busulfan [42], and the lack of need for monitoring. With the potential increase in the use of sirolimus as GVHD prophylaxis, further prospective studies comparing its efficacy and toxicities to MMF are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Bu), with a more predictable bioavailability than oral formulation, has improved the safety profile of BuCy, [9][10][11] but without general improvements in survival compared with TBI. 12,13 MAC regimens such as BuCy or CyTBI would not be advisable for elderly or frail patients due to regimen-related toxicities and an enhanced risk of infections and GVHD, all which contribute to increased non-relapse mortality (NRM). 14,15 Incorporation of fludarabine (Flu) combined with other cytotoxic agents in attenuated doses, the so-called reduced intensity conditioning (RIC) regimens, has enabled patients unsuitable for MAC regimens to safety undergo HSCT procedures.…”
Section: Introductionmentioning
confidence: 99%